Very low concentration of cerium dioxide nanoparticles induce DNA damage, but no loss of vitality, in human spermatozoa. (August 2018) - Préaubert, L.; Tassistro, V.; Auffan, M.; Sari-Minodier, I.; Rose, J.; Courbiere, B.; Perrin, J.
Abstract: Cerium dioxide nanoparticles (CeO2 NP) are widely used for industrial purposes, as in diesel, paint, wood stain and as potential therapeutic applications. The Organization for Economic Cooperation and Development included CeO2 NP in the priority list of nanomaterials requiring urgent evaluation. As metal nanoparticles can cross the blood-testis barrier, CeO2 NP could interact with spermatozoa. The genotoxicity of CeO2 NP was demonstrated in vitro on human cell lines and mouse gametes. However, the effects of CeO2 NP on human spermatozoa DNA remain unknown. We showed significant DNA damage induced in vitro by CeO2 NP on human spermatozoa using Comet assay. The genotoxicity was inversely proportional to the concentration (0.01 to 10 mg·L −1 ). TEM showed no internalization of CeO2 NP into the spermatozoa. This study shows for the first time that in vitro exposure to very low concentrations of cerium dioxide nanoparticles can induce significant DNA damage in human spermatozoa. These results add new and important insights regarding the reproductive toxicity of priority nanomaterials, which require urgent evaluation. Highlights: First report of the genotoxicity of cerium dioxide nanoparticles on human sperm Very low concentrations of cerium dioxide nanoparticles induce significant DNA damage in sperm Genotoxicity inversely proportional to the concentration (0.01 to 10 mg·L −1 )